Semiotic Ideologies - Leone, Massimo, (Literature and Cultural Studies E-Books Online, Collection 2024., 2024)
This book offers a comprehensive exploration of language and semiotic ideologies, focusing on how societies construct meaning through verbal and non-verbal communication. It distinguishes itself by adopting a novel approach that bridges linguistics, semiotics, and anthropology. The research dives into uncharted territory, shedding light on the intricate connections between language, culture, and cognition, offering a perspective less common in traditional linguistics or semiotics. Throughout the book, the reader will encounter rare, illustrative examples showcasing the rich tapestry of human communication. Additionally, previously undisclosed historical data adds depth to the analysis, providing fresh insights. This work is designed for scholars seeking a deeper understanding of meaning-making processes and their cultural variations. It also serves as a resource for those interested in the complex interplay of language and semiotics in everyday life.